Outcome of Snodgrass urethroplasty by modifying tubularization and dartos layer in Erbil - Fattah, Jalal Hamasalih; Kakahmed, Hawkar Abdulla; Al-Ibraheem, Nihad Pauls (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Snodgrass first described the tubularized, incised plate (TIP) urethroplasty for distal hypospadias repair in 1994. This study aimed to find out whether there is any difference in the fistula rate with single versus double layer tubularization, and the use of ventral versus dorsal dartos layer. Methods: Between May 2009 and July 2014, tubularized incised plate urethroplasty was performed for correction of hypospadias in Erbil for 112 patients with age ranging from 1-32 years. Five patients were excluded from the study because of lack of adequate follow up. Data were analyzed using the statistical package for the social sciences. Results: Urethral fistula occurred in seven cases (6.5%).The use of an additional reinforcing second layer for the tubularization had a significant effect on decreasing the fistula formation (P = 0.05). The fistula rate was slightly lower with dorsal dartos flap (5.4%) than ventral dartos flap (7.8%). Conclusion: The urethral plate, when dissected, should be thick enough to allow for tubularizationin two layers. Both dorsal and ventral dartos flaps are effective in preventing urethral fistula.